Academic writing performance paradox: students’ negotiation during the inventing stage - Miftachudin, Miftachudin (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Many university students continue to struggle with academic writing, albeit they have passed the supporting courses of language content and skills. Such a condition becomes paradoxical as the subjects of this research, the 7th-semester students of the English Education Department at UIN Salatiga in the academic year 2025, experience similar phenomena. The students encounter issues in all stages of academic writing, especially during the inventing stage, in which they have to understand the topic, brainstorm ideas, and develop an outline before continuing to the next stages of drafting, revising, and editing. The inventing stage becomes the focus, as it defines and directs the global aspect in writing before they can develop their ideas. This research tries to understand the students’ challenges during the inventing stage of academic writing, and simultaneously concludes their strategies in negotiating those issues. From the Focus Group Discussion with 144 students, the researcher found that students encounter several challenges during the process of writing in the inventing stages in the areas of self-efficacy and motivation, understanding assignments and topics, brainstorming and idea generation, and developing an outline and forming a working thesis. To respond those challenges, the students develop strategies such as formulating motivation and support, finding reference, free listing ideas, and making a mind map. This analysis can contribute to the practical knowledge for further discussion and support the improvement of academic writing in higher education.